Exploring knowledge, attitudes, practices, and determinants regarding emergency contraception use among female university students in Goma, Democratic Republic of the Congo: a cross-sectional study - Patricia Lukusa Mishika; Olivier Mukuku; Amos Kamundu; Kaymarlin Govender; Stanislas Okitotsho Wembonyama; André Kabamba Mutombo (Contraception and Reproductive Medicine)
Abstract Introduction Emergency contraception is an essential method for preventing unintended pregnancies, especially after unprotected sexual intercourse. However, knowledge, attitudes, and practices related to emergency contraception among university students remain underexplored, particularly in low-resource settings such as Goma, Democratic Republic of the Congo. The objective of this study is to assess the knowledge, attitudes, practices, and determinants influencing the use of emergency contraception among female students in Goma. Methods A cross-sectional survey was conducted with 677 female students from two universities in Goma who were selected via a cluster sampling method. Data were collected via a preestablished questionnaire, and participants were interviewed after providing consent. The data were analysed via STATA 16, with chi-square tests to compare variables, considering a significance threshold of 5%. Results A total of 625 (92.32%) students reported being aware of emergency contraception, and 80.32% demonstrated good knowledge of it. In terms of attitudes, 533 (85.28%) students had positive attitudes towards emergency contraception. Among the 625 students who were familiar with emergency contraception, 416 had engaged in sexual intercourse, with 294 (70.67%) having utilized emergency contraception. Factors significantly linked to emergency contraception use included being single (adjusted OR = 1.9 [95% CI: 1.1–3.2]), possessing good knowledge (adjusted OR = 3.0 [95% CI: 1.6–5.8]), and having a positive attitude (adjusted OR = 2.4 [95% CI: 1.1–4.9]). Conclusion Although the students demonstrated good awareness of emergency contraception and its utilization, the high frequency of emergency contraception use underscores the importance of promoting knowledge about conventional contraceptive methods. It is crucial to enhance educational campaigns within universities to mitigate the elevated risk of unsafe abortions.